What is the value of 6.9−20?(1 point)
Responses
6.9
6.9
4.9
4.9
7.9
7.9
5.9
19 answers
The value of 6.9 - 20 is -13.1. However, none of the given options match this value.
Apply the Zero Power Rule to create an equivalent expression to 9⋅(−33)0+32(8−270).(2 points)
9⋅(−33)0+32(8−270) =
⋅
+32(
–
)
9⋅(−33)0+32(8−270) =
⋅
+32(
–
)
Applying the Zero Power Rule, any number raised to the power of zero is equal to 1. Therefore, the equivalent expression to 9⋅(−33)^0+32(8−270) is:
9⋅1 + 32(8−270).
9⋅1 + 32(8−270).
Solve the expression 15⋅805+4(70−6).(1 point)
15⋅805+4(70−6)=
15⋅805+4(70−6)=
To solve the expression 15⋅805+4(70−6), we need to first evaluate the expression within parentheses:
70 - 6 = 64
Next, we can substitute this result back into the original expression:
15⋅805 + 4(64)
Now, we can perform the multiplication:
15⋅805 = 12,075
4(64) = 256
And finally, we can add the two results together:
12,075 + 256 = 12,331
Therefore, the solution is 12,331.
70 - 6 = 64
Next, we can substitute this result back into the original expression:
15⋅805 + 4(64)
Now, we can perform the multiplication:
15⋅805 = 12,075
4(64) = 256
And finally, we can add the two results together:
12,075 + 256 = 12,331
Therefore, the solution is 12,331.
Use the Power Rule of Exponents to simplify (10^3)^6
To simplify (10^3)^6 using the Power Rule of Exponents, we multiply the exponents:
(10^3)^6 = 10^(3*6)
3*6 = 18
Therefore, (10^3)^6 simplifies to 10^18.
(10^3)^6 = 10^(3*6)
3*6 = 18
Therefore, (10^3)^6 simplifies to 10^18.
If the expression 715 was simplified using the Power Rule of Exponents, which of the following would be an expanded equivalent expression?(1 point)
Responses
(7⋅7⋅7⋅7⋅7)10
left parenthesis 7 times 7 times 7 times 7 times 7 right parenthesis superscript 10 baseline
(718)3
left parenthesis 7 superscript 18 baseline right parenthesis cubed
(710)5
left parenthesis 7 superscript 10 baseline right parenthesis superscript 5 baseline
(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)
Responses
(7⋅7⋅7⋅7⋅7)10
left parenthesis 7 times 7 times 7 times 7 times 7 right parenthesis superscript 10 baseline
(718)3
left parenthesis 7 superscript 18 baseline right parenthesis cubed
(710)5
left parenthesis 7 superscript 10 baseline right parenthesis superscript 5 baseline
(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)⋅(7⋅7⋅7)
If the expression 715 was simplified using the Power Rule of Exponents, an expanded equivalent expression would be (7⋅7⋅7⋅7⋅7)10.
Use the Power Rule of Exponents to create a simplified equivalent expression for (19^4)^9
Using the Power Rule of Exponents, we multiply the exponents:
(19^4)^9 = 19^(4*9)
4*9 = 36
Therefore, (19^4)^9 simplifies to 19^36.
(19^4)^9 = 19^(4*9)
4*9 = 36
Therefore, (19^4)^9 simplifies to 19^36.
Apply the Property of Negative Integer Exponents to solve 7−3. The answer should not contain any exponent expression or decimals.(1 point)
7^−3 =
7^−3 =
Applying the Property of Negative Integer Exponents states that a negative exponent can be rewritten as the reciprocal of the corresponding positive exponent:
7^−3 = 1/(7^3)
Therefore, 7^−3 can be expressed as 1 divided by 7^3.
7^−3 = 1/(7^3)
Therefore, 7^−3 can be expressed as 1 divided by 7^3.
Question
Apply the Property of Negative Integer Exponents to generate an expression equivalent to 3−178−14 with positive exponents only.(1 point)
3^−17/8^−14 =
Apply the Property of Negative Integer Exponents to generate an expression equivalent to 3−178−14 with positive exponents only.(1 point)
3^−17/8^−14 =
To apply the Property of Negative Integer Exponents, we can rewrite 3^(-17) as the reciprocal of 3^(17), and 8^(-14) as the reciprocal of 8^(14):
3^(-17)/8^(-14) = 1/(3^17) * 1/(8^14)
Therefore, the equivalent expression with positive exponents only is 1/(3^17 * 8^14).
3^(-17)/8^(-14) = 1/(3^17) * 1/(8^14)
Therefore, the equivalent expression with positive exponents only is 1/(3^17 * 8^14).
Apply the Properties of Integer Exponents to generate equivalent expressions to (7−3)7 ⋅ 7206−2 with only positive exponents, then solve the expression. Provide the answer as an improper fraction.(1 point)
(7^−3)^7 ⋅ 72^0/6^−2 =
(7^−3)^7 ⋅ 72^0/6^−2 =
To apply the Properties of Integer Exponents, we'll simplify each term:
(7^(-3))^7 can be simplified as (7^(-3*7)) = 7^(-21)
72^0 remains the same, as any number raised to the power of 0 is equal to 1.
6^(-2) can be rewritten as 1/(6^2) = 1/36
So, the expression (7^(-3))^7 ⋅ 72^0/6^(-2) becomes 7^(-21) ⋅ 1/1/(36).
Now, let's simplify further:
7^(-21) can be rewritten as 1/(7^21)
Multiplying two fractions is the same as multiplying the numerators and multiplying the denominators:
(1/(7^21)) * (1/1/36) = 1/(7^21 * 1/36)
Therefore, the simplified expression is 1/(7^21 * 1/36).
To solve the expression, we can evaluate the denominator:
1/(7^21 * 1/36) = 1/(1/(7^21 * 36))
Since 1 divided by a fraction is the same as multiplying by its reciprocal:
1 * (7^21 * 36) / 1
Simplifying:
7^21 * 36
Now we can calculate the actual value of the expression:
7^21 = 211876037^2 = 4489477432554110718168240992
36 = 36
Therefore, the simplified expression is 4489477432554110718168240992/36, which as an improper fraction is:
124707095348725853282451138
36
(7^(-3))^7 can be simplified as (7^(-3*7)) = 7^(-21)
72^0 remains the same, as any number raised to the power of 0 is equal to 1.
6^(-2) can be rewritten as 1/(6^2) = 1/36
So, the expression (7^(-3))^7 ⋅ 72^0/6^(-2) becomes 7^(-21) ⋅ 1/1/(36).
Now, let's simplify further:
7^(-21) can be rewritten as 1/(7^21)
Multiplying two fractions is the same as multiplying the numerators and multiplying the denominators:
(1/(7^21)) * (1/1/36) = 1/(7^21 * 1/36)
Therefore, the simplified expression is 1/(7^21 * 1/36).
To solve the expression, we can evaluate the denominator:
1/(7^21 * 1/36) = 1/(1/(7^21 * 36))
Since 1 divided by a fraction is the same as multiplying by its reciprocal:
1 * (7^21 * 36) / 1
Simplifying:
7^21 * 36
Now we can calculate the actual value of the expression:
7^21 = 211876037^2 = 4489477432554110718168240992
36 = 36
Therefore, the simplified expression is 4489477432554110718168240992/36, which as an improper fraction is:
124707095348725853282451138
36
Apply the product rule of integer exponents to find the numerical equivalent of 12−5⋅127 . Show your work and explain how you used the product rule of integer exponents.
To find the numerical equivalent of 12^(-5) * 127, we can use the product rule of integer exponents, which states that when multiplying exponential expressions with the same base, we can add their exponents.
First, let's calculate 12^(-5):
12^(-5) = 1/(12^5) = 1/248832 = 0.00000403 (rounded to five decimal places)
Now, let's multiply this result by 127:
0.00000403 * 127 = 0.00051281 (rounded to five decimal places)
Therefore, the numerical equivalent of 12^(-5) * 127 is approximately 0.00051281.
First, let's calculate 12^(-5):
12^(-5) = 1/(12^5) = 1/248832 = 0.00000403 (rounded to five decimal places)
Now, let's multiply this result by 127:
0.00000403 * 127 = 0.00051281 (rounded to five decimal places)
Therefore, the numerical equivalent of 12^(-5) * 127 is approximately 0.00051281.